Health inequality aversion, e-learning interventions, and personality tests an experimental study - Ortiz, Gabrielle Jahn A.; Bulacan, Hanna Charisse B.; Capuno, Joseph J. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
This paper looks into health inequality aversion and aims to determine whether personality factors, personal characteristics, and e_learning interventions may influence an individual_s level of such aversion. To perform this research, we conducted a classroom experiment attended by 99 students from the University of the Philippines (UP)_Diliman who have taken at least three units of economic course as of the first semester of A.Y. 2018 to 2019. The participants were asked to choose between two hypothetical health programs that affect the life expectancy of two contrasting groups. We utilized elearning interventions in order to test whether there is strong evidence to suggest that those interventions can correct or help mitigate inequality aversion. The data collection mode and experimental framework is adapted from Cookson et. al._s [2018] study in the University of York, UK. Using ordered probit regression and non_parametric tests of significance, we were able to show that participants are generally inequality averse, but the e_learning interventions used in the experiment were able to influence the respondents_ views on health justice, thus, influencing the level of their inequality aversion. Further, the results also show that the personality traits of agreeableness and conscientiousness have substantial effects on one_s perception of health justice.
Thesis (B.S. Economics) -- University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) -- Students; Aversion -- Economic aspects -- Philippines; Medical economics -- Philippines